Impact of Pentoxifylline and Vitamin E on Ribavirin-Induced Haemolytic Anaemia in Chronic Hepatitis C Patients: An Egyptian Survey - M. Assem; M. Yousri (International Journal of Hepatology)
Background/Aim. We evaluate the impact of combined pentoxifylline and high-dose vitamins E to standard antiviral treatment on RBV-induced haemolytic anaemia. Patients and Methods. Selected 200 naïve chronic HCV patients, were randomized to receive either the standard antiviral therapy (peginterferon α-2b and RBV) plus pentoxifylline (800 mg) and high-dose vitamin E (1000 iu) daily (combined group) or received standard antiviral therapy plus placebo only (control group). They were followed up during treatment course and for 6 months posttreatment to assess the occurrence of anaemia and virological response, respectively. Results. RBV dose modification due to anaemia were significantly less in combined group (8.5 versus 21.5%. P<.05).Withdrawal, secondary to sever anemia (Hb<8.5 gm%), was recorded only in 6 (28.6%) patients of the control group. Both (ETR) and (SVR) were significantly higher in combined group than control group by both intention-to-treat analysis (71 versus 56%, P<.05 and 66 versus 49%, P<.05) and per-protocol analysis (85.5 versus 70.9%, P<.05 and 79.5 versus 62%, P<.05). Conclusion. Pentoxifylline and vitamin E can ameliorate RBV-associated haemolysis; improve compliance and virologic clearance when combined with the standard antiviral therapy in patients with chronic hepatitis C.